Effect of monogastric and ruminant gastrointestinal conditions on in vitro aflatoxin B1 adsorption ability by a montmorillonite - Magnoli, Alejandra Paola (2013)
The main objective of this study was to evaluate the interference of environment components on the in vitro evaluation of aflatoxin B1 adsorption capacity of sodium bentonite under simulated gastrointestinal conditions of monogastric and ruminant animals. Sodium bentonite showed a high aflatoxin B1 affinity with all of the assays. Langmuir or sigmoid isotherms were found in different assays. Both the affinities and the surface excesses at monolayer saturation were affected by the buffer components. The specific influence of ions in each buffer solution was investigated. A significant decrease in the surface excess at monolayer saturation was observed under ionic strength control. A change in the isotherm shape from sigmoidal to Langmuir was observed with the increase in the sodium chloride concentration. This was attributed to the decrease in the importance of lateral interaction between adsorbed toxin molecules compared with surface-molecules interactions under a high salt coverage. The presence of rumen fluid components in the adsorption environment decreased the aflatoxin B1 maximum adsorption capacity of sodium bentonite. Despite the high affinity of this adsorbent to capture aflatoxin B1, different substances present in the environment could affect the adsorption capacity, at least at low toxin concentrations that mimic chronic exposure. The environment of the gastrointestinal tract, in either monogastric or ruminant animals, affect in vivo aflatoxin B1 adsorption by sodium bentonite and should be taken into account when an in vitro performance evaluation is done.